Back to the future? The challenges of reforming vocational education and training (VET) systems: a critical analysing of Namibia's current VET reform - Grossmann, M; Naanda, R (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2006)
Vocational Education and Training systems are important elements of countries' economic development strategies. Improving the skills and knowledge of the workforce is crucial for achieving or maintaining economic competitiveness, especially in a context of progressing globalisation. As a consequence, governments around the world are engaging in improving their respective VET systems. The role of vocational education and training (VET) is regarded as key to economic development. In the same context, the Namibian government has initiated a comprehensive reform of its VET system. More than 10 years after passing the Vocational Training Act in 1994, the VET system still experiences many weaknesses in terms of high failure rates in trade examinations, high drop-out rates and not fully matching employers' skill needs. Many of the weaknesses have been known for a long time and various reform initiatives have been designed in the past, but the majority of them have not been implemented successfully. In the context of Namibia's Vision 2030 to become a newly industrialised economy by the year 2030, the education and training sector is again subject to comprehensive reform. The aim of reforming the VET sector is to improve its management, introduce competency based training standards to increase access, improve the responsiveness of skills supply to skills demand and increase the financial base through the introduction of a levy. The purpose of the paper is to analyse in greater detail the prospects of the current VET reform initiative and to identify factors that are likely to influence the outcome of the reform. One central question is: why, given past experiences, should the current reform initiative which is much broader and complex than in the past, be successful this time? The paper argues that the current reform looks promising in scope, but many caveats exist that might limit its successful implementation. Among the greatest dangers are a neglect of the micro-level of reform implementation due to an insufficient involvement of trainees and instructors, a low involvement of the private sector and the inappropriateness of introducing a training levy and the resulting lack of required financial resources.